Structure and Phase Transitions of Genipin, An Herbal Medicine and Naturally Occurring Cross-Linker - Trevor, Susannah L; Butler, Micheal F; Adams, Sarah; Laity, Peter R; Burley, Jonathan C; Cameron, Ruth E (Crystal growth & design, 2008)
The naturally occurring cross-linking agent genipin has recently been the subject of biomedical research both in the creation of hydrogel structures and as a potential active agent in its own right. In this study several methods of specimen preparation were used to isolate and stabilize crystalline genipin material. The thermodynamic properties of the genipin crystals and their phase changes were investigated using differential scanning calorimetry techniques. Single crystal and powder X-ray diffraction (XRD) confirmed two separate polymorphic phases denoted form I and form II. The structures were resolved, and the XRD traces were indexed, and both forms were found to be monoclinic. Genipin forms I and II were also isolated through methanol evaporation crystallization. Form II was formed through this route when the crystallization was accompanied by polymerization of a fraction of the genipin. The materials were also tested under in situ heated, X-ray diffraction conditions at a synchrotron radiation source. Genipin forms I and II were shown to have melting temperatures of around 121 and 101 °C, respectively.